Masyarakat sebagai Garda Terdepan dalam Menghadapi Illegal Fishing: Studi Penelitian di Pulau Rempang Kota Batam - Idham Idham; Juhrin Pasaribu; Kaspol Jihad; Ikhlas Muhammad; Al Jatmuazam; Muhammad Haris Fadillah; Khairil Hidayat; Puti Lindung Bulan; Aditya Azhar; Shandy Herizaldi (Kajian Ilmiah Hukum dan Kenegaraan, 2023)
Purpose: The purpose of this study is to determine the level of understanding and awareness of the people of Rempang Island regarding the impact and threat of illegal fishing by foreign fishermen on maritime resources and socio-economic life. Knowing the obstacles and potential faced by the people of Rempang Island plays an active role as the front line in efforts to prevent and eradicate illegal fishing. Methodology: The method used is a nomative approach, namely through literature studies, and an empirical approach, namely through field research, by conducting a series of interviews with respondents and informants to obtain field data. Results: The results showed that the people of Rempang Island had a varied understanding of the threat of illegal fishing by foreign fishermen, where most fishermen who interact directly with this practice understand the negative impact on maritime resources and marine ecosystems. However, there is still a group of people who are not fully aware of the long-term impacts of these activities. Although the people of Rempang Island face significant obstacles, such as a lack of resources, education, and coordination in efforts to prevent and eradicate illegal fishing, they also have great potential because of community cohesiveness, traditional knowledge of waters, and solidarity of local fishermen.